Резильєнтність економіки та економіка резильєнтності - Череватський, Д.Ю. (Економіка промисловості, 2023)
Резильєнтність як категорія механіки означає здатність пружних тіл відновлювати свою форму після механічного тиску. На тлі пандемії SARS COVID-19 та інших глобальних катаклізмів поняття резильєнтності як стресостійкості набуває все більшого поширення в економічній науці. Ідеться навіть про парадигмальну зміну Індустрії 4.0 з переходом до Індустрії 5.0, для якої характеристика резильєнтності економіки має бути визначальною, а самій індустрії відводиться роль драйвера необхідних трансформацій.
Досить розповсюдженою версією резильєнтності в економіці є здатність екосистеми, бізнесу, суспільства долати шоки та продовжувати функціонувати приблизно таким самим чином. Мета статті полягає в конкретизації поняття резильєнтності для потреб промисловців.
Із застосуванням прикладу, яким є кумулятивна крива собівартості експортерів металургійного вугілля, доведено, що резильєнтність мікро-, мезо- або макроекономіки залежить від сполучення природних (якість родовища, наприклад), географічних (близькість до портів, розвиненість залізничного сполучення та ін.), технологічних чинників і економіко-політичної кон’юнктури.
Парадигму Індустрії 5.0 принципово відрізняє інша «точка складання» – перехід від властивої Індустрії 4.0 неоліберальної моделі капіталізму, яка має під собою «примат акціонерів» і націленість на максимізацію прибутку, до моделі, заснованої на ESG-управлінні (Environmental, Social and Corporate Governance). Другим головним моментом Індустрії 5.0 є прагнення досягти на засадах розгортання регенерації відходів найбільшої автономності економічних структур.
Відзначені факти здатні суттєво вплинути на практику підприємств і регіонів щодо забезпечення їх резильєнтності. Resilience as a category of mechanics means an ability of elastic bodies to restore their shape after mechanical pressure. Against the background of the SARS Covid-19 pandemic and other global cataclysms, the concept of resilience as stress resistance is gaining more and more popularity in economic science. It is even about the paradigmatic change of Industry 4.0 to Industry 5.0, the characteristic of economical resilience for which should be significant, while the industry itself is given the role of necessary transformations’ driver.
A fairly widespread version of resilience in the economy is the ability of the ecosystem, business and society to cope with shocks and continue to function approximately the same way. The mission of this work, its purpose is to specify the concept of resilience to the needs of industrialists.
The category of resilience, by its very name, is an allusion to Hooke's law, which is also called the law of elasticity. Any force applied to the body causes its (body) deformation, the size of which, according to Hooke's law, depends on the force itself and the inherent rigidity of the body. As long as the deformations grow linearly (in proportion to the effort), the body retains its elasticity and returns to its original dimensions after the load is removed. This happens until the load does not exceed the limit of proportionality, beyond which the elongation of the sample occurs without increasing the force with subsequent destruction of the body. The task of maintaining resilience, thus, comes down to knowing the nature of the development of deformations of a specific material – the economy of the enterprise, the region, the national economy – and preventing the loading of the "sample" beyond its inherent level of proportionality. Thus, it makes sense to accept that each company has its own ‘rigidity’ and characteristic ‘deformations’ of the state. Each company has its own production function, which, in the case of using the Cobb-Douglas model, is the dependence of output on labor and capital costs. The inherent rigidity of the economic structure determines the elasticity of its functioning. The long-term impact of adverse forces leads not only to a reduction in production, but also to the closing of production facilities, the dismissal of personnel, which causes a further decline in production and the development of a vicious circle up to the liquidation of the business structure itself due to the complete economic/commercial impracticality of its existence.
Using the example of the cumulative cost curve of metallurgical coal exporters, it is proved that the resilience of any micro-, meso- or macroeconomy depends on a combination of natural (quality of the deposit, for example), geographical (proximity to ports, development of railway connections etc.), technological factors and the economic and political situation.
The paradigm of Industry 5.0 is fundamentally distinguished by another "assembly point" – the transition from the neoliberal model of capitalism, which has the "primacy of shareholders" and the goal of maximizing profit, to a model based on the principles of ESG (from Environmental, Social, and Corporate Governance). The second main point of Industry 5.0 is the desire to achieve the greatest autonomy of economic structures.
The noted points can significantly influence the practice of enterprises and regions in terms of ensuring their resilience.